2023
DOI: 10.1108/ijlm-04-2022-0158
|View full text |Cite
|
Sign up to set email alerts
|

Designing circular supply chains in start-up companies: evidence from Italian fashion and construction start-ups

Abstract: PurposeThe theory of complex adaptive systems (CASs) represents an interesting perspective to study the characteristics of circular supply chains (CSCs). In this regard, the current literature lacks evidence regarding coordination and integration mechanisms, characteristics of the environment and emerging system properties of CSCs. This paper aims to fill this gap and focuses on how and why companies design (i.e. configure and coordinate) their CSCs and what value these design choices help to create across dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Lack of awareness among people and insufficient infrastructure were identified as major barriers in Expanded Polystyrene (EPS) supply chain. Enablers for implementing circularity include support from top management, environment-friendly organizational culture and collaboration across the supply chain echelons (Ciccullo et al. , 2023; Tseng et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of awareness among people and insufficient infrastructure were identified as major barriers in Expanded Polystyrene (EPS) supply chain. Enablers for implementing circularity include support from top management, environment-friendly organizational culture and collaboration across the supply chain echelons (Ciccullo et al. , 2023; Tseng et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) concluded that support by managers, collaboration across the SC and willingness to accept and promote organizational change could enhance industrial performance. Ciccullo et al. (2023) reiterated the significance of coordination among the supply chain actors to achieve circularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting a complex adaptive systems perspective, Ciccullo et al (2023) explore why and how start-ups design CSCs. Case studies of five Italian start-ups in the fashion and construction industries show their CSC design employ open and closed-loop circularity logic.…”
Section: Insights From the Special Issuementioning
confidence: 99%
“…Adopting a complex adaptive systems perspective, Ciccullo et al . (2023) explore why and how start-ups design CSCs.…”
Section: Insights From the Special Issuementioning
confidence: 99%